Diasporic Roots/Circular Routes: Kamin Mohammadi’s Search for Home in The Cypress Tree; A Love Letter to Iran (2011) - Delshad, Parisa (Miscelánea: A Journal of English and American Studies, 2023)
This paper explores Kamin Mohammadi’s position regarding the discourses of national belonging through the scrutiny of her circular route from England to Iran. Reflecting the interrelation between identity, home and the modern nation-state, The Cypress Tree: A Love Letter to Iran (2011) recounts the story of Mohammadi’s journey back to Iran in search of a singular self. It recounts her story of growing up in Iran and England and the reason behind her displacement from both of these countries in 1979 and 1997. Indebted to Stuart Hall’s take on the diaspora, Gaston Bachelard’s reading of home and Homi Bhabha’s notion of hybridity, this paper rejects the synonymy between home and home country as well as exclusive belonging intrinsic to nationalism. The aim of this paper is to read Mohammadi’s ultimate choice to settle down in England as a challenge to the homogenizing forces of nationalism that inhibited her sense of belonging to Britain and drew her toward Iran. As she embraces a hybrid identity by telling her circular story, beginning and ending in London, her literary contribution is a way to dismantle the link between belonging and the nation-state, as well as a challenge to the alleged homogeneity of the nation-states to which she belongs.